Simulating Troublesome Contexts: How Multiple Roles within Ward-Based Simulations Promote Professional Nursing Competence - Corbally, Melissa; Kirwan, Anne; O’Neill, Carla; Kelly, Mary (International Journal of Practice-based Learning in Health and Social Care, 2018)
Nursing care is multifaceted and is practised within complex healthcare environments. Although the concept of competence itself is tenuous (Watson et al. 2002), achievement of nursing competencies remains an essential prerequisite for nurse registration in Ireland. The domains of nursing competence are: professional/ethical practice; holistic approaches to care and the integration of knowledge; organization and management of care; personal and professional development; and interpersonal relationships (An Bord Altranais 2005). At a conceptual level, these can be likened, somewhat, to threshold concepts insofar as they represent important transitions of practice and understanding. In this article, we illustrate how a ward-based simulation exercise with evolving scenarios and multiple role performances mimics ‘troublesome contexts’. We find that this exercise successfully promotes both nurse competence and understanding of threshold concepts through the embodiment of multiple identities (e.g. nurse, patient, relative, observer, etc.). Evaluations of this activity amongst a cohort of final year nursing students have consistently identified the transformative nature of this activity, particularly when acting in the ‘patient’ role. In this article, we describe the processes inherent in this simulation exercise and how the multiple layers of complexity are achieved. The very act of performing multiple identities and roles within an evolving complex environment we suggest, results in a consequential, transformed view (Meyer and Land 2003) of values, attitudes and behaviours in addition to enhancing nursing competence. Evidence of this is demonstrated in evaluations of the debriefing exercise undertaken immediately following simulation.